Correlation of Salivary Thiocyanate Levels and Oral Cytological Changes in Smokers - Silwal, Radha Baral; Ojha, Bidhata; Bajracharya, Dipshikha; Silwal, Ganesh (Journal of College of Medical Sciences-Nepal, 2020)
Introduction: Smokers are found to have higher salivary thiocyanate (SCN) concentration compared to normal non-smokers. This elevated level of the SCN in the saliva of smokers may be responsible for oral cancer risk among smokers through nitrosation process. The objective of the study is to estimate salivary thiocyanate levels in tobacco smokers and non-smokers and correlate the levels of thiocyanate with cytomorphological changes in oral mucosa. Methods: This is a comparative cross-sectional study conducted among 40 non-smokers and 40 smokers in outpatient department of Kantipur Dental College. Salivary thiocyanate level was estimated from the saliva sample. Cytological atypia, cytomorphometric changes and micronuclei frequency was estimated from smear from buccal mucosa. Results: Mean salivary thiocyanate level in smokers (3.16 Mm/l 1.61 Mm/l) was higher compared to non-smokers (0.95Mm/l 0.54 Mm/l) which was statistically significant (P<0.001). There were also more atypical changes in smoker than that found in nonsmokers. The mean nuclear cytoplasmic ratio was also higher in smokers compared to nonsmokers which was statistically significant (P<0.001). Similarly, the micronuclei frequency in smokers (1.79 0.76) was also found higher compared to micronuclei frequency in non-smokers (1.24 0.74) which was statistically significant (P=0.002). However, the correlation between salivary thiocyanate level and cytomorphometric changes was weak. Conclusions: Estimation of salivary thiocyanate level and cytological changes are noninvasive, painless and prove to be an efficient tool in screening a large population as well as in aiding motivation of individuals for withdrawal of tobacco smoking.